Studi Literatur : Gambaran Stres Perawat saat Melaksanakan Pelayanan Nursing Home Care - Sandra Restuti; Ati Surya Mediawati; Udin Rosidin (Universitas Malahayati Lampung, 2023)
ABSTRACT The incidence of stress in home care nurses is common in the world. High job demands can impact on nurse stress. Therefore, it will have an effect to work performance and the quality of care provided. In addition, other impacts can range from burnout to depersonalization. The purpose of this study aimed to describe the stress of nurses when carrying out nursing home care services. This research design used was a narrative review method. The variable in this study was the stress of nurses when carrying out nursing home care services. All literature was obtained through the PubMed. The keywords used were “stress” or “job stress” and “nursing home care” or “home care” or “home health care” and “negative impact. 38 journal articles were founded that were appropriate and analyzed using tables based on stress factors. Based on the results of the study, the most common sources of stress were workload and conflicts between nurses. The forms of stress shown by nurses are confusion, feelings of insecurity, and loss of work motivation. The bad effects of stress are physical and mental health problems to the desire to leave work. 74.6% of nurses working in nursing home care experience stress. Henceforth, it is necessary to conduct research that addresses the relationship between workload and conflict between nurses and stress events in home care nurses. Keywords: Nurse, Nursing Home Care, Stress ABSTRAK Kejadian stres pada perawat home care banyak terjadi di dunia. Tuntutan pekerjaan yang tinggi dapat menimbulkan stres. Hal ini berpengaruh terhadap performa kerja dan kualitas asuhan yang diberikan. Selain itu, dampak lainnya dapat berupa burnout hingga depersonalisasi. Penelitian ini bertujuan untuk mengetahui gambaran stres perawat saat melaksanakan pelayanan nursing home care. Rancangan penelitian ini menggunakan narrative review. Variabel dalam penelitian ini adalah stres perawat saat melaksanakan pelayanan nursing home care. Seluruh literatur didapatkan melalui database PubMed. Kata kunci yang digunakan yaitu “stress” or “job stress” and “nursing home care” or “home care” or “home health care” and “negative impact. Didapatkan 38 jurnal artikel yang sesuai dan dilakukan analisis menggunakan tabel berdasarkan faktor terjadinya stres. Berdasarkan hasil penelitian, sumber stres yang paling banyak ditemukan adalah beban kerja dan konflik antar perawat. Bentuk stres yang ditunjukkan perawat berupa kebingungan, perasaan tidak percaya diri, dan kehilangan motivasi kerja. Dampak buruk dari stress yaitu gangguan kesehatan fisik dan mental hingga keinginan untuk meninggalkan pekerjaannya. 74,6% perawat yang bekerja di pelayanan nursing home care mengalami stress. Untuk selanjutnya perlu dilakukan penelitian yang membahas hubungan antara beban kerja serta konflik antar perawat dengan kejadian stres pada perawat home care. Kata Kunci : Nursing Home Care, Perawat, Stress